2017
DOI: 10.1016/j.yclnex.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol drinking, brain mitochondrial DNA, polyunsaturated fatty acids and effects of dietary anthocyanins

Abstract: Anthocyanins Brain Polyunsaturated fatty acids Mitochondrial DNA s u m m a r yBackground: This study aimed at exploring whether moderate ethanol drinking may have adverse effects on the fatty acids composition and on mitochondrial DNA (mtDNA) of rat brain. A secondary aim was to examine whether dietary antioxidant anthocyanins (ACN) can be protective. Methods: One group of rats received ethanol 12% and another water as an exclusive liquid to drink for 8 weeks. In order to test the impact of ACN consumption, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the CNS, a specific innate immune system, consisting of resting or activated glial cells, protects the nervous system against pathogens or injuries, but an excessive or prolonged inflammatory response may contribute to neuronal apoptosis and may facilitate the progression of neurodegenerative diseases (Russo and Mcgavern, 2015) Many dietary ACNs contain multiple ACNs compounds with neuroprotective effects. Dietary ACNs from blue corn protected brain from the mitochondrial DNA common deletion (mtDNA CD) induced by a moderate ethanol consumption (Demeilliers et al, 2017). Finally, we showed that the administration of ACN-rich purple corn extract has a protective effect on the development of orofacial allodynia in an in vivo model of inflammatory trigeminal pain, and that it reduces trigeminal macrophage infiltration and microglial activation both in vivo and in vitro (Magni et al, 2018).…”
Section: Neuroprotective Effectsmentioning
confidence: 81%
See 1 more Smart Citation
“…In the CNS, a specific innate immune system, consisting of resting or activated glial cells, protects the nervous system against pathogens or injuries, but an excessive or prolonged inflammatory response may contribute to neuronal apoptosis and may facilitate the progression of neurodegenerative diseases (Russo and Mcgavern, 2015) Many dietary ACNs contain multiple ACNs compounds with neuroprotective effects. Dietary ACNs from blue corn protected brain from the mitochondrial DNA common deletion (mtDNA CD) induced by a moderate ethanol consumption (Demeilliers et al, 2017). Finally, we showed that the administration of ACN-rich purple corn extract has a protective effect on the development of orofacial allodynia in an in vivo model of inflammatory trigeminal pain, and that it reduces trigeminal macrophage infiltration and microglial activation both in vivo and in vitro (Magni et al, 2018).…”
Section: Neuroprotective Effectsmentioning
confidence: 81%
“…Many dietary ACNs contain multiple ACNs compounds with neuroprotective effects. Dietary ACNs from blue corn protected brain from the mitochondrial DNA common deletion (mtDNA CD) induced by a moderate ethanol consumption ( Demeilliers et al, 2017 ). Finally, we showed that the administration of ACN-rich purple corn extract has a protective effect on the development of orofacial allodynia in an in vivo model of inflammatory trigeminal pain, and that it reduces trigeminal macrophage infiltration and microglial activation both in vivo and in vitro ( Magni et al, 2018 ).…”
Section: Pharmacological Activities Of Acns: An Overview On Molecularmentioning
confidence: 99%
“…For instance, ACNs found in blue maize have been shown to shield the brain from the mitochondrial DNA common deletion that is caused by moderate ethanol intake. ACN-rich purple corn extract lowers trigeminal macrophage infiltration and microglia activation both in vivo and in vitro and protects against the development of orofacial allodynia in an in vivo model of inflammatory trigeminal pain ( 152 , 153 ). Moreover, purple corn has neuroprotective effects equivalent to the anti-inflammatory properties of acetylsalicylic acid, which do not alter microglial activity ( 152 , 153 ).…”
Section: Medicinal Naturally Occurring Substances Used In the Treatme...mentioning
confidence: 99%
“…In vivo, many anthocyanin compounds have shown neuroprotective and anti-inflammatory effects, comparable to those of acetylsalicylic acid [ 85 , 86 ]. According to several epidemiological and human intervention studies, anthocyanin administration could be a reducing factor for the risk of cardiovascular diseases, due to their anti-thrombotic effects [ 87 , 88 , 89 , 90 ].…”
Section: Polyphenols and Tanninsmentioning
confidence: 99%